A Proportional Sentencing Norms for Accomplices in Indonesian Corruption Cases: Norma Hukuman yang Proporsional untuk Pelaku Pendamping dalam Kasus Korupsi di Indonesia - Ansori, Ansori; Sugiri, Bambang; Aprilianda, Nurini; Noerdajasakti, Setiawan (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Corruption is an extraordinary crime requiring effective legal measures. Specific Background: In Indonesia, accomplices in corruption crimes receive the same punishment as principal offenders, raising concerns about fairness. Knowledge Gap: Current laws do not differentiate culpability levels, leading to potential injustices. Aims: This study examines the proportionality of sentencing norms for accomplices in corruption cases. Results: Findings show that equal sentencing contradicts proportional justice and creates legal inconsistencies. Novelty: The study highlights conflicts between the Anti-Corruption Law and the Criminal Code, advocating for reform. Implications: Policy adjustments are needed to align sentencing with justice principles, ensuring fairness in anti-corruption enforcement. Highlights: Unequal Punishment: Accomplices receive the same sentence as principal offenders, raising fairness concerns. Legal Inconsistency: The Anti-Corruption Law conflicts with the Indonesian Criminal Code on culpability. Policy Reform Needed: Sentencing should align with proportional justice to ensure fairness in law enforcement. Keywords: Proportionality, Accomplices, Offence